VizieR Online Data Catalog: TESS observations of Cepheid stars (Plachy+, 2021) - Plachy, E.; Pal, A.; Bodi, A.; Szabo, P.; Molnar, L.; Szabados, L.; Benko, J. M.; Anderson, R. I.; Bellinger, E. P.; Bhardwaj, A.; Ebadi, M.; Gazeas, K.; et al. (VizieR Online Data Catalog, 2021)
The NASA Transiting Exoplanet Survey Satellite (TESS) observations consist of ~27 day long measurements with constant pointing to a 24°x96° field of view, called a "sector". In this paper, we present the first results on Cepheid stars observed with TESS, covering the first five out of 26 sectors of its primary 2yr near all-sky mission (2018-2019). (3 data files).
Keywords: Optical; Photometry; Stars: variable